Ultraviolet-B (UV-B) and ultraviolet-C (UV-C) radiation as elicitors of flavonoid production and effects on genetic stability of Jatropha curcas Linn. Callus cultures - Alvero, Erika Marie R.; Ungson, Lilian B. (Quezon City Institute of Biology, College of Science, University of the Philippines Diliman, 2010)
Jatropha curcas Linn. callus cultures were grown in Murashige and Skoog (MS) medium supplemented with naphthalene-acetic acid (NAA) and kinetin. The degree of genetic variation in the control cultures and their capacity to produce the flavonoids, apigenin, vitexin and isovitexin were examined though RAPD analysis using 10 arbitrary decamer primers and HPLC respectively. After 9 weeks in culture and 4 subculture cycles, the calli formed were found to be genetically equivalent to the mother plant indicating that no somaclonal variation (SV) occurred under such growth conditions. HPLC analysis found that even though vitexin and isovitexin are the dominant flavonoids in the leaves, they were not detected in the callus extracts and despite the absence of detectable levels of apigenin in the leaves, a small amount was found in the callus extracts. These results suggest a correlation between the degree of differentiation and biosythesis of flavonoids in plant tissues. Overall, findings reveal that elicitation through UV-B irradiation is more effective strategy to induce flavonoid production in dedifferentiated J. curcas cultures that have lost their capacity to produce the flavonoids normally synthesized in intact organs.
Thesis (M.S. Biology)--University of the Philippines Diliman
Keywords: Plant cell development